A Study on Finite Element Method: An Overview: A comprehensive overview of the Finite Element Method (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The finite element method (FEM) is a numerical examination technique for acquiring estimated answers for a wide variety of building issues. A finite element model of an issue gives a piecewise guess to the overseeing equations. The fundamental reason of the FEM is that an answer locale can be logically displayed or approximated by supplanting it with a gathering of discrete elements. Since these elements can be assembled in a variety of ways, they can be utilized to speak to exceedingly complex shapes and significant commitments of Indian mathematicians to the numerical parts of the finite element method over the most recent multi decade 2008-2017. We quickly follow out the verifiable inceptions of the theme in India and abroad. An area on the method itself is incorporated so this audit is available to anyone with a foundation in incomplete differential equations and numerical techniques for understanding it.